THE ANALYSIS OF STUDENTS’ DIFFICULTIES AND LEARNING MOTIVATION IN LEARNING SPEAKING PRONUNCIATION AT THE TENTH GRADE OF MA AT-TADZKIR KALIAREN - Lyana Rohmawati; Sri Wahyuni (Language Circle: Journal of Language and Literature, 2025)
This study aims to investigate the students’ difficulties and students’ motivation in learning speaking pronunciation. The type of research in this study is descriptive research which aims to describe an information in the current state. This research was conducted at MA At-Tadzkir Kaliaren. The research subjects are students of 10th grade with total subjects in this research are one class, 19 students consist of 14 males and 5 females. Data collection methods used in this study were questionnaires and interviews. The result of this study indicates the learning difficulties in learning speaking pronunciation for students of 10th grade MA At-Tadzkir Kaliaren have a high category and students' motivation is in the medium category. In addition, I also found some factors that influence the students' difficulty in speaking (1) confidence, (2) lack of vocabulary, (3) pronunciation, and (4) media while the factors that influence learning motivation 1) seriousness in learning English, (2) the influence of friends in doing assignments, (3) boredom.